PENGARUH JURNALISTIK GAME ONLINE MOBILE LEGENDS TERHADAP PRESTASI AKADEMIK SISWA SMA NEGERI 1 GUNUNG MERIAH ACEH SINGKIL - Said M Yusren Ilham Fajeri; M Yoserizal Saragih (Jurnal Ilmiah Global Education, 2023)
This research aims to know the influence of journalistic online game mobile legends on the academic achievement of high school students Negeri 1 Gunung Meriah Aceh Singkil. This study uses quantitative descriptive methods. This study is a field study. (field research). Data sources in this study include primary data obtained directly from respondents and secondary data acquired indirectly through relevant literature. Data collection techniques in this study include non-participatory observation and spread of elevators. (kuesioner). Data analysis techniques in this study include validity ujiting, reliability ujiting, classical assumption ujiting, and hypothesis ujiting through IBM SPSS devices. The results of this study showed that the value of the variable regression coefficient X (b) yielded a value of 0.686 which shows that the journalistic variable online game mobile legends has a positive influence on the academic variable of high school students Negeri 1 Gunung Meriah Aceh Singkil which means that every increase in the unit of variable journalistics online game mobil legends will affect the academical population of students of State 1 High School Mount Meriah Ace Singkil by 0.686. Based on the ujit determination coefficient that the impact of the value of the R Square (R2) factor of 0.515 or 51.5%. then it can be concluded that the influence of the journalistic online game mobile legends (X). against the academic variable of high school students State 1 Gunung Meriah Aceh Singkil 51.5%.